Effects of short-term cold exposures on blood leukocyte parameters in rats of different ages - Lomako, Viktoria; Pirozhenko, Liudmyla; Shylo, Oleksandr (Problems of Cryobiology and Cryomedicine, 2026)
The short-term intermittent cold exposures (STCE) at 10 and –12°C on the ratio of leukocyte types in the blood of 6-, 12-, and 24-month-old rats, as well as the changes in integral leukocyte indices (ILIs) were studied. Under both STCE regimens, the total number of leukocytes in 6-month-old animals increased, while in 12- and 24-month-old ones it decreased, the percentage of segmented neutrophils in all age groups augmented, and that of lymphocytes reduced. The allergization and immunoreactivity indices decreased, and cellular immunity predominated (except for 24-month-old rats at –12°C). After STCE 10°C, the Garkavi adaptation index decreased in rats of all age groups, but at STCE –12°C it reduced in 6-month-old ones only. The innate immunity was activated in rats of all age groups at 10°C, but at –12° it was only in 6- and 12-month-old animals. Under both STCE regimens, the 6- and 12-month-old rats showed decreased adaptive immunity and increased inflammation. Changes in ILIs after STCE –12°C were the highest in 6-month-old animals and the lowest in 24-month-old ones. Probl Cryobiol Cryomed. 2025; 35(3): 123—129